Central African Republic : Fourth Review Under the Extended Credit Facility Arrangement, Requests for Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, Augmentation of Access, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2018)
The economy of the Central African Republic (C.A.R.), a fragile state, is recovering gradually. Following the 2013 crisis, macroeconomic conditions have stabilized: growth has resumed, inflation has declined, domestic revenues have recovered, and debt ratios have decreased. The outlook, however, is clouded by persistent fragility amid repeated eruptions of violence. Half of the population depends on humanitarian assistance. Stronger and more inclusive growth is necessary to make a dent into widespread poverty. The government's economic strategy is supported by a three-year arrangement under the Extended Credit Facility (ECF)-launched in July 2016-with total access of SDR 133.68 million (120 percent of quota).